Crystal structure of poly[diaqua-(μ2-1,3-di(1H-imidazol-1-yl)propane-κ2N:N′)-bis(μ2-5-carboxybenzene-1,3-dicarboxylato-O,O′:O″)-aqua-di-zinc dihydrate solvate], C27H28N4O16Zn2 - Zhang Yan; Wang Jia-Xin; Huang Pei-Pei; Wu Ting-Ting; Gao Jia-Hao; Lu Jiu-Fu (Zeitschrift für Kristallographie - New Crystal Structures)
C27H28N4O16Zn2, monoclinic, C2/c (no. 15), a = 13.0720(3) Å, b = 15.7589(5) Å, c = 15.7589(5) Å, β = 95.373(3)°, V = 3062.48(18) Å3, Z = 4, Rgt(F) = 0.0499, wRref(F2) = 0.1059, T = 294 K.